Synergistic interactions between transcription factors control expression of the apolipoprotein AI gene in liver cells. - Widom, R L (1991)
The gene coding for apolipoprotein AI (apoAI), a plasma protein involved in the transport of cholesterol and other lipids in the plasma, is expressed predominantly in liver and intestine. Previous work in our laboratory has shown that different cis-acting elements in the 5'-flanking region of the human apoAI gene control its expression in human hepatoma (HepG2) and colon carcinoma (Caco-2) cells. Hepatocyte-specific expression is mediated by elements within the -256 to -41 DNA region relative to the apoAI gene transcription start site (+1). In this study it was found that the -222 to -110 apoAI gene region is necessary and sufficient for expression in HepG2 cells. It was also found that this DNA region functions as a powerful hepatocyte-specific transcriptional enhancer. Gel retardation and DNase I protection experiments showed that HepG2 cells contain proteins that bind to specific sites, sites A (-214 to -192), B (-169 to -146), and C (-134 to -119), within this enhancer. Site-directed mutagenesis that prevents binding of these proteins to individual or different combinations of these sites followed by functional analysis of these mutants in HepG2 cells revealed that protein binding to any one of these sites in the absence of binding to the others was not sufficient for expression. Binding to any two of these sites in any combination was sufficient for only low levels of expression. Binding to all three sites was essential for maximal expression. These results indicate that the transcriptional activity of the apoAI gene in liver cells is dependent on synergistic interactions between transcription factors bound to its enhancer.